2021
DOI: 10.1002/pra2.524
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Relevance of Information as a Social Justice Issue: An Interactive Panel Discussion

Abstract: Relevance is a notion whose meaning and purpose have been widely discussed in information retrieval research. The ultimate aim of relevance-what Tefko Saracevic has called the "you know" principle-is to ensure that users have the information necessary to meet their goals. What is often missing from this discussion is a critical assessment of who gets to decide what information is relevant, under what circumstances, and for what purposes-especially in relation to marginalized populations. The limited discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Specifically, the theory of intersectionality offers a robust framework to examine interlocking racialized, colonial, ableist, and heteropatriarchal systems of power and oppression (Combahee River Collective 1978). While intersectional theory was explicitly applied by CAIS/ACSI and ASIS&T scholars (for example, Winberry et al 2021;Lieu, Allard, and Oliphant 2019), we also observed that feminist theories were often used in conjunction with other complementary critical theories, such as decolonization, critical race, and queer theory. Applying an intersectional lens can make visible and facilitate exploration of specific frameworks of social power and their consequences for information and research contexts.…”
Section: Feminisms and Related Critical Theoriesmentioning
confidence: 82%
“…Specifically, the theory of intersectionality offers a robust framework to examine interlocking racialized, colonial, ableist, and heteropatriarchal systems of power and oppression (Combahee River Collective 1978). While intersectional theory was explicitly applied by CAIS/ACSI and ASIS&T scholars (for example, Winberry et al 2021;Lieu, Allard, and Oliphant 2019), we also observed that feminist theories were often used in conjunction with other complementary critical theories, such as decolonization, critical race, and queer theory. Applying an intersectional lens can make visible and facilitate exploration of specific frameworks of social power and their consequences for information and research contexts.…”
Section: Feminisms and Related Critical Theoriesmentioning
confidence: 82%
“…Essa foi uma oportunidade para discutir, entre outras, temáticas sobre racismo durante a pandemia de COVID-19 (Chong & Chen, 2021), antirracismo na profissão bibliotecária (Tang et al, 2021), discriminação e informação LGBTQ+ (Brown et al, 2021). Além disso, a relevância da informação como uma questão de justiça social foi debatida em um painel de discussão com especialistas (Winberry et al, 2021).…”
Section: Deia Na Biblioteconomia E Ciência Da Informaçãounclassified